2023
DOI: 10.1111/jors.12640
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on economies of scale in local public service provision: A meta‐analysis

Abstract: The standard theory of optimal jurisdictional size hinges on the existence of economies of scale in the provision of local public goods and services. However, despite its relevance for forced local amalgamation programs and related policies, the empirical evidence on the existence of such economies of scale remains elusive. The main goal of this paper is to produce an updated and comprehensive quantitative review of the existence of economies of scale in the provision of local public goods using a meta‐analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Another study found a similar trend between energy intensities and the volume of water produced among water treatment plants; the larger the volume of water produced, the less energy-intensive the process was found to be [31]. These trends have not only been found in the water industry, but also in services such as transportation, garbage collection, public schooling, and electricity [32,33].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Another study found a similar trend between energy intensities and the volume of water produced among water treatment plants; the larger the volume of water produced, the less energy-intensive the process was found to be [31]. These trends have not only been found in the water industry, but also in services such as transportation, garbage collection, public schooling, and electricity [32,33].…”
Section: Discussionmentioning
confidence: 72%
“…The reported values were considered statistically significant if the p-value was less than or equal to 0.05, if the R 2 value was equal to or greater than 0.8, or if the RMSE value was between 0.2 and 0.5. In a literature review conducted on economies of scale in the local public service provision, out of seventy-six analyzed studies, thirty-five (46%) used the ordinary least squares test, the largest percentage for a single test [33]. To remain consistent with the findings from this study and others, we selected this test.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the concentration of a large number of older adults living in the same area (NORCs) generates economies of scale [36]. This scenario presents a beneficial opportunity for the government to provide home care and support services at a lower cost within these communities [37]. The concentration of older adults makes it easier and more cost-effective to deliver services, as resources can be centralized and used more efficiently.…”
Section: Discussionmentioning
confidence: 99%